Weakening of the actualization of Pancasila values in national and state life - Zainul Djumadin (Jurnal Sosial Sains dan Komunikasi, 2023)
Pancasila, as the basis of the state, has a key role in shaping the character and identity of the nation. However, through observations of social, political and cultural developments, there are indications that the actualization of Pancasila values has decreased in daily life practices. This research aims to investigate the phenomenon of weakening the actualization of Pancasila values in national and state life in Indonesia. This research uses a qualitative approach where this research method involves documentary analysis, surveys and interviews to explore the public's understanding of Pancasila values and the extent to which these values are reflected in public behavior and policies. The research results show that the actualization of Pancasila values in national and state life requires a comprehensive approach. Revitalizing formal education, especially through Citizenship Education (PKn) subjects, is a crucial step to align Pancasila values with real life. Apart from that, the example of leaders, both formal and informal, is a major factor in moving society towards realizing the values of Pancasila. The role of educators as educational leaders is also very important, where the example and guidance provided by teachers can shape the character of students as agents of change who actualize Pancasila values in everyday life. With this approach, it is hoped that society can build a strong foundation to create a national culture that is inclusive and united in diversity.